Сопровождение студентов-инофонов в инклюзивной среде вуза - Подобин, Алексей Евгеньевич; Щербинина, Ольга Станиславовна (International Dialogues on Education Journal, 2016)
The present educational situation requires new approaches when working with heterogeneous groups of learners at different levels of schooling—from preschool to higher-education institutions. There are different types of students in Russian higher-education institutions: students with handicaps, with HIA (Health Impact Assessment), without parents, gifted students, foreigners, migrants and others. The Kostroma State University, which is currently a university funded by the Kostroma region, offers the possibility of obtaining the most diverse educational qualifications. These heterogenous groups have a considerable amount of international students. To this day, the personnel of this university already has gained interesting experiences through working with this type of students, which are presented in this article.